Assessment of Oxidative Stress and Antioxidant Status In Children With Acute Lymphoblastic Leukemia at Diagnosis (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Oxidative stress is an inevitable accompaniment in almost every disease process including cancer. As Acute Lymphoblastic Leukemia (ALL) is a disease very much susceptible to oxidative stress, assessment of Plasma Malondialdehyde (MDA) and Erythrocyte Glutathione (GSH) levels are thought of as suitable parameters to detect oxidative stress and antioxidant status respectively in children with ALL. The purpose of the study was to assess the oxidative stress together with antioxidant defense by estimation of plasma MDA and erythrocyte GSH in children with acute lymphoblastic leukemia at diagnosis.Materials and methods: This prospective case-control study was conducted in the Department of Pediatric Hematology and Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU) in collaboration with the Department of Pharmacology, BSMMU from March 2019 to December 2021. Sixty two (62) children with acute lymphoblastic leukemia were recruited (Group-B) at diagnosis through purposive sampling and 20 control (Healthy children) were enrolled (Group-A). Plasma malondialdehyde and erythrocyte glutathione of these children (Group-A and Group-B) were estimated through spectro photometric measurements and results were compared between two groups of these two parameters by unpaired t-test.Results: The plasma malondialdehyde levels of Group-B were 3.28±0.40 mol/L (Means ±SD). Plasma malondialdehyde levels of Group-A were 1.17±0.57 mol/L. The difference was statistically significant (p=0.0001). Erythrocyte glutathione levels of group-B were 2.59±1.46mg/g (Means ±SD). On the contrary erythrocyte glutathione levels of group-A were 4.55±1.17mg/g. The difference was statistically significant (p=0004). These results evolve excess MDA production and GSH depletion in children with ALL.Conclusion: Observation from the study suggested that products of lipid per oxidation (MDA) in children with ALL remained at significantly higher (p=0.0001) at diagnosis. The study also x that malignancy induced stress, body’s endogenous antioxidant was being depleted in attempts to detoxify the products of oxidative injury.JCMCTA 2024; 35 (2) : 10-16